Analisis Adverse Drug Reactions (ADRs) Penggunaan Antibiotik Terhadap Penyakit Community Acquired Pneumonia (CAP) Pada Balita Di RSUD Kota Mataram - Fanny Dwi Febriyana; Fitry Apriliany; Muh. Isnaini Zuhri (Department of Pharmacy, Bumigora University, 2023)
Pneumonia is an infection that causes inflammation of the lung tissue so that the lung sacs are filled with infectious agents and are the main cause of infant mortality in the world. The initial therapy for pneumonia is the use of antibiotics. Irrational use of antibiotics can lead to ADRs. Adverse Drug Reactions (ADRs) often cause obstacles in the implementation of treatment. The purpose of this study was to see how ADRs influence the use of antibiotics on the clinical outcomes of pneumonia patients. The method analytic observational study using a cross-sectional design which is carried out prospectively, by collecting data on inpatients. Data were obtained from interviews with patients and/or patient families using the Naranjo questionnaire, as well as searches of patient medical records during the period January - March 2023. Analysis of ADRs on the use of antibiotics on outcomes was analyzed by the Likelihood ratio. This study was dominated by patients aged <2 years (61.5%) with improved outcomes (97.15%). The results obtained showed that there was no significant relationship between ADRs using antibiotics and patient outcomes with a p>0.05 (p=0.798). The conclusion of this study is that there is no effect of ADRs using antibiotics on patient outcomes.